Estimation of saturated air water content at elevated pressures using simple predictive tool - Bahadori, Alireza; Vuthaluru, Hari (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2011)
In a compressed air system, condensed water vapor can have corrosive effects on metals and wash out protective lubricants from tools, equipments and pneumatic devices. To protect against such undesirable effects in a compressed air system, it is necessary to be able to predict the water content of air in order to design and apply the appropriate type of drying to be used in the system. In this work, a simple predictive tool, which is easier than currently available models and involves a fewer number of parameters, requiring less complicated and shorter computations, is presented here for the prediction of water content of air as a function of temperature and relative humidity as well as for compressed saturated air as a function of pressure and temperature using an Arrhenius-type asymptotic exponential function. The proposed method predicts the amount of air water content for temperatures up to 45 °C, pressures up to 1400 kPa and relative humidities up to 100%. Estimations are found to be in excellent agreement with the reliable data in the literature with average absolute deviation being less than 1.4 and 2.2% for atmospheric air and saturated compressed air, respectively. The tool developed in this study can be of immense practical value for engineers and scientists to have a quick check on the water content of atmospheric air and saturated compressed air at various conditions without opting for any experimental measurements. In particular, engineers and scientists would find the approach to be user-friendly with transparent calculations involving no complex expressions.